Facilitated transport separation of CO2 and H2S by supported liquid membrane based on task-specific protic ionic liquids - Lingling Peng; Mingzhen Shi; Xiaomin Zhang; Wenjie Xiong; Xingbang Hu; Zhuoheng Tu; Youting Wu (Green Chemical Engineering, 2022)
Selective separation of CO2 and H2S from CH4 is of importance to the natural gas upgrading because of its corrosivity. As is well known, amine group can recognize reversibly CO2 and H2S with a moderate interaction. With this in mind, this work prepared a series of amine-functionalized supported-protic-ionic-liquid membranes (SPILMs) for the selective separation of CO2 and H2S from CH4. For comparison, aprotic ionic liquid membrane was also prepared for natural gas sweetening. The effect of temperature and transmembrane pressure difference on the permeability of single gas and ideal selectivity of CO2/CH4 and H2S/CO2 were studied. Facilitated transport mechanism was studied by NMR spectra. The permeability of CO2 in primary amine functionalized [DMPDAH][Tf2N]-based membrane decreases with the increasing transmembrane pressure, indicating a typical feature of facilitated transport membrane. The permeability of CO2 and the ideal selective of CO2/CH4 are as high as 2000 barrers and 53.2 at 313.2 K in [DMPDAH][Tf2N] membrane, significantly higher than those in conventional ILs membrane. It is anticipated that these amine-functionalized SPILMs can provide alternative insight for the selective separation of CO2 and H2S from CH4.